2023
DOI: 10.1098/rspa.2023.0081
|View full text |Cite
|
Sign up to set email alerts
|

The density and pressure of helium nano-bubbles encapsulated in silicon

Abstract: The 1 s 2 → 1 s 2 p ( 1 P ) excitation in compressed helium atoms in either the bulk material or encapsulated in a bubble is shifted to energies higher than in the free atom. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…This behavior for the He 1s→2p transition has been associated with the short-range Pauli pseudo-repulsion of the 2p-electron wave function with the ground-state orbital of neighboring atoms [ 59 , 60 ]. This effect has also been measured at the microscopic scale by monitoring individual bubbles in a transmission electron microscope using STEM–EELS [ 24 , 27 , 61 ]. For the case of gaseous Ne, the K-shell excitation has also been previously investigated through EELS using small-angle inelastic scattering of 2.5 keV electrons [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This behavior for the He 1s→2p transition has been associated with the short-range Pauli pseudo-repulsion of the 2p-electron wave function with the ground-state orbital of neighboring atoms [ 59 , 60 ]. This effect has also been measured at the microscopic scale by monitoring individual bubbles in a transmission electron microscope using STEM–EELS [ 24 , 27 , 61 ]. For the case of gaseous Ne, the K-shell excitation has also been previously investigated through EELS using small-angle inelastic scattering of 2.5 keV electrons [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…An exhaustive microstructural characterization also showed that gas content and nanobubble size and shape are finely tunable [ 17 , 24 , 25 ]. Due to the high density and pressure of He trapped in the nanobubbles [ 24 , 25 , 26 , 27 ], the He-charged Si films have been proposed as “solid targets” for nuclear reaction studies in our previous works [ 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…This behavior for the He 1s→2p transition has been associated to the short-range Pauli pseudo-repulsion of the 2p-electron wave function with the ground-state orbital of neighboring atoms [58,59]. This effect has also been measured at the microscopic scale monitoring individual bubbles in a transmission electron microscope by STEM-EELS [24,27,60]. For the case of gaseous Ne, the K-shell excitation has been also previously investigated by EELS spectroscopy using small-angle inelastic scattering of 2.5 keV electrons [61].…”
Section: Spectroscopic Study Of the Ne-kedge Absorption Spectra Of Ne...mentioning
confidence: 88%
“…An exhaustive microstructural characterization also showed that gas content and nanobubbles size and shape are finely tunable [17,24,25]. Due to the high density and pressure of He trapped in the nanobubbles [24][25][26][27], the He-charged Si films have been proposed as "solid-targets" for nuclear reaction studies in our previous works [28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%